The maple syrup industry in Canada and the United States: challenges and potential strategies towards a more sustainable development - Qingbin Wang; Emmanuel Owoicho Abah; Mark Cannella (Frontiers in Sustainable Food Systems, 2025)
While maple syrup as an iconic sweetener predominantly produced in Canada and the United States has experienced significant growth in the past four decades, the industry faces many climate, economic, and policy challenges. This study reviews the industry’s development, analyzes the major challenges faced by the industry, and derives recommendations for addressing such challenges and moving towards more sustainable development. Specifically, data from Canadian and U.S. government agencies and other sources is used to trace the industry’s development, examine the correlation between U.S. and Canadian maple syrup production and producer prices, assess the market impacts of Quebec’s production quota system, and discuss potential strategies. Historical data indicates that the maple syrup industry in both nations has experienced significant growth in production since the early 1980s but also increased volatility in both sap yield and maple syrup output, downward trends in producer prices, rising production costs, and increasing impacts of trade disputes and retaliations. Empirical analysis suggests that the production quota system in Quebec started in 2004 has limited the region’s production growth as compared to other major production regions, stabilized its producer prices around a level that is lower than the prices received in the late 2000s, and likely affected the prices received by U.S. maple syrup producers. Major recommendations from this study include shifting the focus from supply-side interventions to include more demand-side enhancement, increasing investment in technical innovation and climate mitigation, developing more value-added maple syrup products, and strengthening the marketing and promotion efforts to increase the demand for maple syrup in the domestic and foreign markets.